Biopolymers Online 2002
DOI: 10.1002/3527600035.bpol3a14
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Polymerization to Polyesters

Abstract: Introduction Historical Outline Ring‐opening Polymerization of Cyclic Monomers Polymerization of Lactones Polymerization of Other Cyclic Monomers Copolymerization of Cyclic Monomers Single‐step Synthesis of End‐functionalized Polyesters Polymerization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 141 publications
0
11
0
Order By: Relevance
“…Characteristic nature of enzymatic catalysis was fully used for controlling the stereochemistry, chemoselectivity, and regioselectivity for the ester products, which are often needed in the total synthesis of complicated structured natural products or in the preparation of pharmacologically active compounds. In polymer chemistry field, synthesis of polyesters by using enzymes as catalyst has been developed almost concurrently, and short or comprehensive review papers on this field have been published from time to time . It is to be noted here that enzymatic polyester synthesis involves several characteristic features of “green polymer chemistry”, which we often pointed out in our previous publications .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Characteristic nature of enzymatic catalysis was fully used for controlling the stereochemistry, chemoselectivity, and regioselectivity for the ester products, which are often needed in the total synthesis of complicated structured natural products or in the preparation of pharmacologically active compounds. In polymer chemistry field, synthesis of polyesters by using enzymes as catalyst has been developed almost concurrently, and short or comprehensive review papers on this field have been published from time to time . It is to be noted here that enzymatic polyester synthesis involves several characteristic features of “green polymer chemistry”, which we often pointed out in our previous publications .…”
Section: Introductionmentioning
confidence: 88%
“…These results initiated to actively study enzyme‐catalyzed polyester synthesis. Thereafter, various lactones of different ring‐size, unsubstituted and substituted, have been polymerized or copolymerized, catalyzed by lipases of different origin . Unsubstituted 4‐ to 17‐membered lactone monomers are given in Scheme .…”
Section: Ring‐opening Polymerization Of Lactonesmentioning
confidence: 99%
“…Enzyme catalysis has provided a new synthetic strategy for a variety of useful biomaterials, most of which would to be difficult to produce using conventional chemical catalysts [48,49,50,51,52,53,54]. For example, tin(II) 2-ethylhexanoate Sn(Oct) 2 , probably the most often used catalyst in the polymerization of cyclic esters, has been approved by FDA as a food additive.…”
Section: Biocatalytic Synthesis Of Polymers For Biomedical Applicamentioning
confidence: 99%
“…Horseradish peroxidase (HRP), an oxidation-catalyzing enzyme with high stability and activity, can catalyze gelation via radical coupling of phenol and aniline derivatives in the presence of exogenous hydrogen peroxide (H 2 O 2 ). 20 Such reactions offer the ability to tune the gelation rate and final gel properties (e.g., stiffness). Notably, Groll et al reported HRP-catalyzed redox-sensitive disulfide crosslinked hydrogels in basic pH conditions (pH 8.5) and without H 2 O 2 but with slow (>110 min) reaction times.…”
Section: Introductionmentioning
confidence: 99%